How much rural is the CAP? - Beatrice Camaioni; Roberto Esposti; Francesco Pagliacci; Franco Sotte (WWWforEurope, 2014)
In this task, research is mostly finalised to analyse how EU policies have been distributed across space. Here, the main focus is on Common Agricultural Policy (CAP) expenditure. The same territorial detail adopted in previous tasks is used (i.e., NUTS 3 level). By analysing CAP expenditure at such a territorial disaggregation level, this work has specifically concentrated on rural, agricultural and environmental policies. Actually, specific CAP measures are directly aimed at tackling those issues. CAP also accounts for a large share of overall EU funds, and it represents one of major drivers of EU spatial development. The methodology of analysis is based on the reconstruction of allocation of EU funds across EU-27 NUTS 3 regions. First, an exploratory analysis of the spatial allocation of CAP expenditure across Europe is assessed. Spatial allocation of CAP expenditure is considered by disentangling specific measures as well (e.g., Pillar One and Pillar Two expenditure, Direct Payment and Market Intervention Measures, Pillar Twos Axes ). Both absolute expenditure levels and expenditure intensity are computed here. Then, through a simple statistical analysis, the correlation between CAP expenditure at NUTS 3 level and regional features, in terms of both rurality and agricultural activity, is assessed.
Keywords: O18; Q01; R12; R58; 330; Economic growth path; European economic policy